Avaliação dos níveis de depressão, ansiedade e sonolência diurna em cuidadores primários de crianças com paralisia cerebral - Marx, Catherine [UNIFESP] (2009)
Purpose: To evaluate depression, anxiety and daily somnolence levels in primary caregivers of children with cerebral palsy (CCP) and trace the relationship with their social-economic conditions and child neurological characteristics, comparing with caregivers of healthy children (CH). Methods: It was a cross-section study with 45 CCP and 50 CH whose children were at the age group between six months and 12 years old. To carry out the interviews, a semi-structured guide was applied. Questions were about children function level, classifying them with help of the GMFCS, rehabilitations undertaken, drugs intake and devices. The caregiver answered personal socio-economic questions; time spent with the child, self-perception about depressive and anxiety symptoms. Sleep pattern and daily somnolence were evaluated with Epworth scale support. In order to diagnose depression, Beck depression inventory (BDI) was used, and the anxiety symptoms were found out throughout state-trait anxiety inventory (STAI). Caregivers were randomly chosen at child neurology ambulatory of the Universidade Federal de São Paulo (UNIFESP/EPM). They were personally invited during their child regular consult or were asked to attend the interview by phone calls. Comparison with randomly chosen CH in general population was carried out. Results: Forty-five CCP and 50 CH were interviewed. The great majority were mothers. CCP had lower level of education and also lower income than CH. They devoted many hours a day to take care of their sick child. The CCP find themselves more anxious then depressive, which was confirmed through BDI and STAI. Being a CCP was a prominent factor to raise depression and anxiety levels. Excessive daily somnolence was greatly related to higher depression levels. However, children impairments and demands did not influence the results at all. Conclusions: Mothers frequently assume the primary caregiving responsibility for a child with chronic disease. The caregiver burden does not allow a career or academic investment causing even greater financial difficulties. Depression, anxiety symptoms and sleep disruption, an association previously described in general population, seems to be a usual problem faced by CCP.